Acute effects of one-leg standing on arterial stiffness in older women: Role of the vision condition and standing dose - Zhou, Zhixiong; Tao, Xiaoli; Zhang, Yuqin; Zhu, Weili (Frontiers in Physiology, 2022)
Objective: One-leg standing has been used exclusively for static balance testing and training purposes. We investigated the acute effects of one-leg standing with open or closed eyes on arterial stiffness in older women, and explored the role of standing dose in arterial stiffness regulation. Methods: Eighteen older women (60 ± 2 years) underwent non-intervention control (CON), one-leg Standing with Open eyes for 2 × 3 min (SO2), one-leg Standing with Closed eyes for 1 × 3 min (SC1), 2 × 3 min (SC2) and 3 × 3 min trial (SC3) in a randomized self-controlled crossover fashion. Arterial stiffness in Cardio-ankle vascular index (CAVI) was measured at baseline (BL), immediately (0 min), 10 min and 20 min after standing. CAVI changes from BL in the same trial (⊿CAVI) were used for analysis. Results: ⊿CAVI of non-standing and standing side did not change with time in CON and SO2 trial. In SC1, SC2 and SC3 trial, ⊿CAVI of the standing side decreased significantly at 0 min compared to their corresponding BL (P < 0.01), and reverted gradually to BL level afterwards, with ⊿CAVI of the non-standing side undergoing no changes. At the time point of 0 min, only in SC2 trial was the ⊿CAVI of standing side significantly lower than that of CON (P < 0.01). Conclusions: One-leg standing with closed eyes, but not open eyes, resulted in transient arterial stiffness improvement in older women. The improvement was restricted to standing leg, and moderate standing dose had maximal benefit on arterial stiffness.